Effects of pretreatment with anticonvulsants on halothane induced liver injury - IIDA, Shinji; OHNISHI, Kunihiko; SAITO, Masayuki; NOMURA, Fumio; HATANO, Hitoshi; OKUDA, Kunio (Kanzo, 1986)
Effects of various anticonvulsants on development of halothane induced liver injury were investigated in human subjects and in experimental animals. Clinical data of 279 cases who underwent brain surgery with halothane anesthesia were analyzed. The incidence of halothane induced liver injury was significantly higher in subjects who were given phenobarbital than in controls (9/100 vs 2/179, p<0.005). Furthermore, effects of three anticonvulsants (phenobarbital, diphenylhydantoin, varproic acid) on halothane hepatotoxicity and halothane metabolism were investigated. In phenobarbital pretreated rats, exposure to halothane under hypoxic conditionsresulted in a significant elevation of S-GPT and centrilobular necrosis of the liver. By contrast, liver injuries were minimal in rats pretreated with either VPA or DPH. Hepatic microsomal P-450 contents and the extent of reductive metabolism of halothane were highest in the phenobarbital pretreated group. These results suggest that patients pretreated with PB may be more susceptible to halothane hepatoxicity, and that VPA and DPH could be substitute for PB.